2017
DOI: 10.3892/mmr.2017.7121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microRNA-26b on proliferation and invasion of glioma cells and related mechanisms

Abstract: Neuroglioma is the most common primary malignant tumor in neurosurgery. Due to its short survival period and high patient mortality rate, neuroglioma is a major challenge in clinics. Elucidating the pathogenic mechanisms and associated molecular targets of neuroglioma can therefore benefit diagnosis and treatment of glioma. Previous studies have established the role of microRNA (miR)‑26b in various tumors, including breast cancer, lymphoma and glioma. Its function and mechanism in neuroglioma, however, remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Even some miRNAs can have anti‐tumor effects. For example, miR‐26 could facilitate apoptosis and inhibit invasion/proliferation of neuroglioma cells via potentiating caspase‐3 activity and downregulating expression of Bcl‐2 . Change in miRNA expression can lead to disturbance in the expression of target protein, inhibition of the expression of tumor suppressor genes, or impairment in cellular processes .…”
Section: Effects Of Melatonin On Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Even some miRNAs can have anti‐tumor effects. For example, miR‐26 could facilitate apoptosis and inhibit invasion/proliferation of neuroglioma cells via potentiating caspase‐3 activity and downregulating expression of Bcl‐2 . Change in miRNA expression can lead to disturbance in the expression of target protein, inhibition of the expression of tumor suppressor genes, or impairment in cellular processes .…”
Section: Effects Of Melatonin On Signaling Pathwaysmentioning
confidence: 99%
“…About 15% of all brain tumors are diagnosed as GBMs, and affects three people per 100 000 annually . Among the malignant tumors of nervous system, GBM has a bad prognosis and creates many economic and psychological problems for patients and families . Some studies point to the effect of hereditary susceptibility and environmental oncogenic agents on the development of GBM .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, miR-26b has been reported to function as a tumor suppressor (20)(21)(22)(23). Li et al (22) reported that miR-26b inhibits the metastasis of colorectal cancer by inhibiting fucosyltransferase 4. miR-26b has also been identified to inhibit proliferation and invasion of neuroglioma cells by downregulating Bcl-2 expression and enhancing caspase-3 activity (23). In OS, miR-26b has been reported to suppress cancer cell proliferation, migration and invasion, and induce OS cell apoptosis by inhibiting glycolysis (20).…”
Section: Introductionmentioning
confidence: 99%